FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADA USAHATANI BAWANG MERAH DI DESA BANJAREJO KECAMATAN NGANTANG KABUPATEN MALANG - Asrianto Asrianto; Bambang Siswadi; Masyhuri Mahfudz (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
AbstractThe purpose of this study is To determine the effect of land area, seeds, manure, TSP fertilizer, pesticides and labor on the production of shallot farming in Banjarejo Village. Analysis of the data used is by multiple regression analysis with cobb-Douglas function. The results of this study are the While the factors that significantly influence the production of shallots are the area of land, seeds and KCL fertilizer while the factors that do not affect the production of shallots are urea, TSP fertilizer, Za fertilizer, drugs and labor. Keyword : Production, onion